Construction of complex three-dimensional vascularized liver tissue model in vitro based on a biphasic cell-laden embedding medium - Weikang Lv; Haoran Yu; Abdellah Aazmi; Tuya Naren; Wanli Cheng; Mengfei Yu; Zhen Wang; Xiaobin Xu; Huayong Yang; Liang Ma (International Journal of Extreme Manufacturing)
Constructing an in vitro vascularized liver tissue model that closely simulates the human liver is crucial for promoting cell proliferation, mimicking physiological heterogeneous structures, and recreating the cellular microenvironment. However, the layer-by-layer printing method is significantly constrained by the rheological properties of the bioink, making it challenging to form complex three-dimensional vascular structures in low-viscosity soft materials. To overcome this limitation, we developed a cross-linkable biphasic embedding medium by mixing low-viscosity biomaterials with gelatin microgel. This medium possesses yield stress and self-healing properties, facilitating efficient and continuous three-dimensional shaping of sacrificial ink within it. By adjusting the printing speed, we controlled the filament diameter, achieving a range from 250 μ m to 1000 μ m, and ensuring precise control over ink deposition locations and filament shapes. Using the in situ endothelialization method, we constructed complex vascular structures and ensured close adhesion between hepatocytes and endothelial cells. In vitro experiments demonstrated that the vascularized liver tissue model exhibited enhanced protein synthesis and metabolic function compared to mixed liver tissue. We also investigated the impact of varying vascular densities on liver tissue function. Transcriptome sequencing revealed that liver tissues with higher vascular density exhibited upregulated gene expression in metabolic and angiogenesis-related pathways. In summary, this method is adaptable to various materials, allowing the rheological properties of the supporting bath and the tissue’s porosity to be modified using microgels, thus enabling precise regulation of the liver tissue microenvironment. Additionally, it facilitates the rapid construction of three-dimensional vascular structures within liver tissue. The resulting vascularized liver tissue model exhibits enhanced biological functionality, opening new opportunities for biomedical applications.